2012
DOI: 10.1093/infdis/jis631
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Transmission of Extensively Drug-Resistant Tuberculosis in a Rural Hospital in South Africa

Abstract: The XDR-tuberculosis epidemic in Tugela Ferry, South Africa, has been highly clonal. However, the epidemic is not the result of a point-source outbreak; rather, a high degree of interconnectedness allowed multiple generations of nosocomial transmission. Similar to the outbreaks of multidrug-resistant tuberculosis in the 1990s, poor infection control, delayed diagnosis, and a high HIV prevalence facilitated transmission. Important lessons from those outbreaks must be applied to stem further expansion of this ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
132
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 40 publications
1
132
1
1
Order By: Relevance
“…2,5,6 A higher proportion of pre-and XDR-TB cases (82%) had an unfavourable outcome, similar to the 80% reported elsewhere in South Africa. 7 Unlike studies in Turkey 8 and in Pakistan, 9 where MDR-TB was more common among women, we had similar proportions of male and female DR-TB cases. However, in our study, being * Missing values were not displayed and were found in the following variables: anti-tuberculosis treatment outcome (n = 4, 1.5%), sex (n = 4, 1.5%), baseline smear (n = 29, 10.7%), oral adherence (n = 42, 15.4%), injectable adherence (n = 62, 22.8%), HIV status (n = 7, 2.6%), baseline culture (n = 40, 14.7%), weight (n = 20, 7.4%) and age (n = 33, 12.1%).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…2,5,6 A higher proportion of pre-and XDR-TB cases (82%) had an unfavourable outcome, similar to the 80% reported elsewhere in South Africa. 7 Unlike studies in Turkey 8 and in Pakistan, 9 where MDR-TB was more common among women, we had similar proportions of male and female DR-TB cases. However, in our study, being * Missing values were not displayed and were found in the following variables: anti-tuberculosis treatment outcome (n = 4, 1.5%), sex (n = 4, 1.5%), baseline smear (n = 29, 10.7%), oral adherence (n = 42, 15.4%), injectable adherence (n = 62, 22.8%), HIV status (n = 7, 2.6%), baseline culture (n = 40, 14.7%), weight (n = 20, 7.4%) and age (n = 33, 12.1%).…”
Section: Discussionmentioning
confidence: 53%
“…This may reflect the provision of antiretroviral treatment to these cases, which we did not assess and which can improve outcomes. 7 Treatment adherence of at least 80% with both oral and injectable drugs was poor. It is unclear why good adherence to injectable drugs did not have a significant effect on unfavourable outcomes; this requires further investigation.…”
Section: Public Health Action Drug-resistant Tb In the Northern Cape 203mentioning
confidence: 99%
“…This is in contrast to the highly publicized outbreak of XDR-TB in HIV-positive individuals due to transmission in Tugela Ferry, South Africa. Similar to the outbreaks of MDR-TB in the 1990s (11)(12)(13), XDR-TB cases among HIV-infected patients often occurred as a result of transmission, because 55% of the cases had no history of TB treatment (14). In China, a recent national survey in 2007 showed that 5.7% of new cases and 25.6% of previously treated cases had MDR-TB, and 8% of MDR-TB cases had developed XDR-TB.…”
mentioning
confidence: 87%
“…From these animal model and epidemiological data, one might conclude that drug resistance incurs a fitness cost leading to lower transmissibility. However, large outbreaks of MDR TB and XDR TB have been recorded (489,490); compensatory mutations that restore fitness but sustain resistance have been identified (224); and recent genotyping efforts have provided strong evidence of the international spread of an MDR M. tuberculosis clone of the Beijing genotype, particularly in East and Central Asia, Eastern Europe, and South Africa (455,491), as well as the large-scale spread of an MDR M. tuberculosis clone of the LAM genotype family in, and beyond, South Africa (492).…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isomentioning
confidence: 99%